PENGGUNAAN MEDIA GAMBAR MOTIF BATIK UNTUK MENINGKATKAN KETERAMPILAN MENDESAIN BATIK TULIS PADA MATA PELAJARAN BATIK KELAS XI TEKSTIL SMKN 5 MALANG - Widjiastuti, Risdwi Soenoe (JADECS (Journal of Art, Design, Art Education & Cultural Studies), 2021)
ABSTRACTThis study aims to determine the most effective teaching methods to improve students' understanding and skills of the batik design. The best method is expected to be implemented so that students will be able to make batik with attractive designs. The study was conducted to 10 students from class XI in SMKN 5 Malang with the methods applied gradually until three times of the learning process. Thus, the learning method that was applied up to three times showed  the best results, as more and more students were able to design creative batik theme.Keyword : Picture,motif,design,written batik